Stability analysis for real-time pseudodynamic and hybrid pseudodynamic testing with multiple sources of delay. - Mercan, Oya
Real-time pseudodynamic (PSD) and hybrid PSD test methods are experimental techniques to obtain the response of structures, where restoring force feedback is used by an integration algorithm to generate command displacements. Time delays in the restoring force feedback from the physical test structure and/or the analytical substructure cause inaccuracies and can potentially destabilize the system. In this paper a method for investigating the stability of structural systems involved in real-time PSD and hybrid PSD tests with multiple sources of delay is presented. The method involves the use of the pseudodelay technique to perform an exact mapping of fixed delay terms to determine the stability boundary. The approach described here is intended to be a practical one that enables the requirements for a real-time testing system to be established in terms of system parameters when multiple sources of delay exist. Several real-time testing scenarios with delay that include single degree of freedom (SDOF) and multi-degree of freedom (MDOF) real-time PSD/hybrid PSD tests are analyzed to illustrate the method. From the stability analysis of the real-time hybrid testing of an SDOF test structure, delay-independent stability with respect to either experimental or analytical substructure delay is shown to exist. The conditions that the structural properties must satisfy in order for delay-independent stability to exist are derived. Real-time hybrid PSD testing of an MDOF structure equipped with a passive damper is also investigated, where observations from six different cases related to the stability plane behavior are summarized. Throughout this study, root locus plots are used to provide insight and explanation of the behavior of the stability boundaries.
Keywords: Delay-dependent stability analysis; Time delay; Restoring force; Real-time hybrid pseudodynamic testing; Real-time pseudodynamic testing